Konstruksi Konsep Geometri Berdasarkan Teori Apos Konteks Budaya Damar Kurung Ditinjau Dari Perbedaan Gender - Octaviyanti, Lensy; Wahyuni, Indah (Radian Journal: Research and Review in Mathematics Education, 2023)
In order to trigger various penetrations in the field of mathematics, researchers conducted a research related to learning mathematics which aims to describe the process of constructing geometric concepts with the cultural context of Damar Kurung in terms of gender based on APOS theory using a qualitative-descriptive approach. Data analysis uses primary data in the form of student work, observations and interviews. The sampling technique used purposive sampling with the criteria of the student concerned having good communication skills. The results showed that based on the percentage of female students, it was much better, namely 81.25% compared to boys, at the scheme stage it only reached 5.8% in the first question, while in question number 2 the percentage of male students in the scheme stage was only reached 11.7%, very far compared to women whose percentage reached 68.75%. The percentage difference is 57.05%. With this percentage, it can be concluded that gender is one of the influences and is the focus for re-doing research related to testing how much influence gender has on solving ethnomathematics-based problems.